2017
DOI: 10.1016/j.compositesa.2017.07.023
|View full text |Cite
|
Sign up to set email alerts
|

A simple chemical approach to regenerating the strength of thermally damaged glass fibre

Abstract: Process-induced strength loss is a major technical barrier to the effective reuse of thermally recycled glass fibres in composite applications. We have developed a novel approach to effectively restore strength in glass fibres through treatment in alkaline solutions. Glass fibres were treated at elevated temperature and experienced significant strength loss found typically after thermal recycling processes. Different alkaline treatments were then applied to the thermally damaged fibres in an attempt to restore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…The dissolution of silicate glass in alkali is well documented in literature [16][17][18]; however, the use of these corrosive substances for strengthening thermally damaged glass fibres is a novel concept; it is believed the reaction of silica (SiO 2 ) with hydroxide ions (OH -) from the alkaline solution [19] leads to a modification of the damaged fibre surface and improves tensile strength. We have found that the strength increase from a short hot alkaline treatment can be achieved at little expense of removing surface materials [11]. This contrasts with the behaviour of HF, which significantly etches the glass fibre surface at its optimum treatment duration of 2.5 min [12].…”
Section: Introductionmentioning
confidence: 43%
See 1 more Smart Citation
“…The dissolution of silicate glass in alkali is well documented in literature [16][17][18]; however, the use of these corrosive substances for strengthening thermally damaged glass fibres is a novel concept; it is believed the reaction of silica (SiO 2 ) with hydroxide ions (OH -) from the alkaline solution [19] leads to a modification of the damaged fibre surface and improves tensile strength. We have found that the strength increase from a short hot alkaline treatment can be achieved at little expense of removing surface materials [11]. This contrasts with the behaviour of HF, which significantly etches the glass fibre surface at its optimum treatment duration of 2.5 min [12].…”
Section: Introductionmentioning
confidence: 43%
“…Due to the harsh conditions employed in this procedure, the glass fibres suffer from a severe loss in their ultimate strength and therefore cannot be reused in many forms of composite applications [7][8][9][10]. We have recently developed a simple chemical approach to address this key issue and have successfully proved that these damaged filaments can be reused as reinforcements again if their strength is restored [11]. It was found that the strength of glass fibres heat-conditioned at 450-600°C can almost triple after a few minutes of immersion in dilute hydrofluoric acid (HF) [12].…”
Section: Introductionmentioning
confidence: 99%
“…The results of single fibre tensile testing displayed a maximum recovery of 75%. Bashir et al [17] carried out a detailed study in order to assess the effectiveness of other alkaline treatments (KOH and LiOH) in restoring the tensile strength of thermally degraded glass fibres. Results suggested that LiOH was unable to regenerate the strength while KOH proved to be a milder glass fibre etchant compared to NaOH, producing improvements in fibre strength only at higher molarity and longer treatment times.…”
Section: Introductionmentioning
confidence: 99%
“…These treatments allow to obtain a closed-loop recycling process [15], resulting in a considerable reduction of the CO 2 produced [18]. These studies on chemical treatments of glass fibres [17,19] demonstrated that the strength regeneration is governed by a dissolution reaction that occurs during the immersion of the fibres in the corrosive solution. In this regard, a controlled dissolution in aqueous HF-solution can be performed to remove the superficial layers of silicate glass [20].…”
Section: Introductionmentioning
confidence: 99%
“…Thomason et al observed a similar effect in E‐glass, using hydrofluoric acid as the etchant and a silane as a protective coating . They dismissed the commercial potential for the process due to the need for HF but later developed another approach using alkaline etching solutions and HCl in a process analogous to the acid/base baths utilized for cleaning laboratory glassware. Phosphate‐based fibers are resistant to HF but are etched by HCl and so an acid etching approach would be much less hazardous to implement commercially for phosphates than the HF/silicate method.…”
Section: Resultsmentioning
confidence: 99%